FAKTOR-FAKTOR YANG MEMPENGARUHI PERGANTIAN KAP PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2012-2013 - Aminuddin, 11.05.52.0148; Poerwati, Rr.Tjahjaning (Students Journal of Accounting and Banking, 2015)
This study aims to examine the effect of financial distress, management turnover, profitability and size of the company to auditor changes. Several previous studies on the turn KAP showed different results. Therefore, it is necessary to study in order to verify the theory about the auditor changes. The data used is the company went public in the period 2012- 2013. The researcher used purposive sampling and obtained a sample of 98 research data. The research data were then tested by logistic regression using SPSS 16 applications to examine the effect of financial distress, management turnover, profitability and size of the company to auditor changes. The results of this study indicate that financial distress, management turnover and profitability do not have significant effect on auditor changes. While firm size have significant effect on auditor changes.Keywords: Financial Distress, Management Turnover, Profitability, Firm Size and Auditor Changes